PHYSICAL CHARACTERISTICS OF WHITE BREAD WITH VARIOUS LEVELS OF PURPLE SWEET POTATO FLOUR SUBSTITUTION - Ifadah, Raida Amelia; Putri, Diwyacitta Antya; Lukitasari, Febriani; Handajani, Sri; Nurlaela, Luthfiyah; Nugraheni, Fitriana (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This study evaluated the effect of wheat flour substitution with purple sweet potato flour on the physical characteristics of white bread. The experiment was conducted using a Completely Randomized Design with a single factor, namely the level of purple sweet potato flour substitution at 0%, 15%, 30%, 45%, and 60%. The physical parameters analyzed included color (L*, a*, b*), texture (firmness), porosity, and dough expansion.The results showed that increasing levels of purple sweet potato flour substitution significantly affected all physical parameters of the bread (p < 0.05). Higher substitution levels resulted in a decrease in lightness (L*) and an increase in a* values, indicating darker crumb and crust color due to the presence of anthocyanin pigments. Bread firmness increased from 6.45 ± 0.13 N in the control sample to 50.16 ± 2.90 N at 60% substitution, while porosity and dough expansion decreased markedly from 45.34 ± 0.42% to 22.13 ± 1.19% and from 89.09 ± 0.02% to 15.71 ± 3.24%, respectively.Substitution of purple sweet potato flour at 30% produced bread with acceptable physical characteristics, characterized by a balanced texture, porosity, and dough expansion. Substitution levels above this threshold resulted in a significant decline in bread quality. These findings indicate that purple sweet potato flour has strong potential as a functional ingredient in white bread formulation. Keywords: flour substitution; physical characteristics; purple sweet potato flour; white bread. Abstrak Penelitian ini bertujuan untuk mengevaluasi pengaruh substitusi tepung terigu dengan tepung ubi jalar ungu terhadap karakteristik fisik roti putih. Penelitian dilakukan menggunakan Rancangan Acak Lengkap (RAL) dengan satu faktor, yaitu tingkat substitusi tepung ubi ungu sebesar 0%, 15%, 30%, 45%, dan 60%. Parameter yang dianalisis meliputi warna (L*, a*, b*), tekstur, porositas, serta daya kembang. Hasil penelitian menunjukkan bahwa peningkatan tingkat substitusi tepung ubi ungu berpengaruh signifikan (p < 0,05) terhadap seluruh parameter fisik roti. Peningkatan substitusi menyebabkan penurunan nilai kecerahan (L*) pada serta peningkatan nilai a*, yang menunjukkan penggelapan warna akibat keberadaan pigmen antosianin. Nilai tekstur meningkat dari 6,45 ± 0,13 N pada roti kontrol menjadi 50,16 ± 2,90 N pada substitusi 60%, sedangkan porositas dan pengembangan adonan mengalami penurunan berturut-turut dari 45,34 ± 0,42% menjadi 22,13 ± 1,19% dan dari 89,09 ± 0,02% menjadi 15,71 ± 3,24%. Substitusi tepung ubi ungu 30% menghasilkan roti dengan karakteristik fisik yang masih dapat diterima, ditandai dengan keseimbangan antara tekstur, porositas, dan daya kembang. Substitusi di atas tingkat tersebut menyebabkan penurunan kualitas fisik roti yang signifikan. Penelitian ini menunjukkan bahwa tepung ubi ungu berpotensi dimanfaatkan sebagai bahan fungsional dalam formulasi roti putih. Kata kunci: karakteristik fisik; roti tawar; substitusi tepung; tepung ubi jalar ungu.